2005
DOI: 10.1093/molehr/gah205
|View full text |Cite
|
Sign up to set email alerts
|

Splice variants of the relaxin and INSL3 receptors reveal unanticipated molecular complexity

Abstract: LGR7 and LGR8 are G protein-coupled receptors that belong to the leucine-rich repeat-containing G-protein coupled receptor (LGR) family, including the thyroid-stimulating hormone (TSH), LH and FSH receptors. LGR7 and LGR8 stimulate cAMP production upon binding of the cognate ligands, relaxin and insulin-like peptide 3 (INSL3), respectively. We cloned several novel splice variants of both LGR7 and LGR8 and analysed the function of four variants. LGR7.1 is a truncated receptor, including only the N-terminal regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 32 publications
3
57
1
Order By: Relevance
“…It has been reported that RXFP1 and Rxfp1 are expressed in different splice variants in humans and mice, whereby often only w100 bp of regions encoding the ectodomain can be missing, thereby making the resulting products nonfunctional (Muda et al 2005, Scott et al 2006. In the present study, the RT-PCR data with primers amplifying the endodomain of the RXFP1 only was not able to resolve the issue of whether splice variants involving the ectodomaincoding region are present or not.…”
Section: Discussioncontrasting
confidence: 58%
“…It has been reported that RXFP1 and Rxfp1 are expressed in different splice variants in humans and mice, whereby often only w100 bp of regions encoding the ectodomain can be missing, thereby making the resulting products nonfunctional (Muda et al 2005, Scott et al 2006. In the present study, the RT-PCR data with primers amplifying the endodomain of the RXFP1 only was not able to resolve the issue of whether splice variants involving the ectodomaincoding region are present or not.…”
Section: Discussioncontrasting
confidence: 58%
“…The dramatic effects of L283F and T222P mutations prove that both hydrophobic core and hydrophilic phase of LRR play an important role in this process. Interestingly, the minor splice variants of LGR7 missing some of the LRRs also failed to be expressed on cell surface membranes in vitro (17).…”
Section: Discussionmentioning
confidence: 99%
“…Ligand Binding Assays-The method to study the binding of 125 I-INSL3 to HEK-293T cells stably transfected with human LGR8 has been described previously (15).…”
Section: Methodsmentioning
confidence: 99%